Surgical approach for the verticalization of the third molar through a miniature screw. Is extraction necessary?. - Harris Ricardo, Jonathan (2022)
Previously, it was reported in the literature that third molars in poor position, such as horizontal, mesial and disto angulated, were a clear indication for tooth extraction. The verticalization of molars with a miniscrew in the mandibular branch corresponds to an ortho-surgical technique in which, through movements on the longitudinal axis of a tooth, a good positioning in the arch and preservation of the tooth is achieved, avoiding extraction. The purpose of this work is to describe the surgical approach and results of the verticalization of an included lower third molar in the mesioangular position, through the placement of a miniature screw using the mandibular branch as anchorage in a 35-year-old female patient.